Light-intensity physical activity and mental ill health: a systematic review of observational studies in the general population - Mireia Felez-Nobrega; Judit Bort-Roig; Ruimin Ma; Eugenia Romano; Matthew Faires; Brendon Stubbs; Emmanuel Stamatakis; Beatriz Olaya; Josep Maria Haro; Lee Smith; Jae Il Shin; Min Seo Kim; et al. (BMC, 2021)
Abstract Background Most of theevidence has focused on examining the influence of moderate-to-vigorous intensity physical activity on mental health, but he role of light intensity physical activity (LIPA) is less understood. The purpose of this systematic review was to assess the relationship between time spent in LIPA and mental ill health across the lifespan. Methods Data were obtained from online databases (Medline, Embase, Scopus, PsychInfo and CINAHL). The search and collection of eligible studies was conducted up to May 28, 2020. Observational studies conducted in the general population and reporting on the association between LIPA (1.6-2.9 metabolic equivalents; either self-reported or device-based measured) and mental ill health were included. Results Twenty-two studies were included in the review (16 cross-sectional and 6 longitudinal). In older adults (≥ 65 years) and adults (18-64 years), the evidence examining the relationship between LIPA and depressive symptoms is mixed. Data on anxiety, psychological distress and overall mental health are scarce, and results are inconclusive. There is no evidence suggesting favorable associations between LIPA and anxiety in college students. Finally, very limited data was found in adolescents (11-17 years) (n = 2 studies) and children (6-10 years) (n = 2 studies), but the evidence suggests that LIPA does not influence mental health outcomes in these age groups. Conclusions This review provided mostly cross-sectional evidence indicating that LIPA may not be associated with mental health outcomes across age groups. Future research efforts employing prospective research designs are warranted to better understand the role of LIPA on mental ill health across age groups.